Redox Status in Canine Leishmaniasis - Fausto Quintavalla; Giuseppina Basini; Simona Bussolati; Gennaro Giuseppe Carrozzo; Antonio Inglese; Roberto Ramoni (Animals, 2021)
The World Health Organization defined leishmaniasis as one of the priority attention diseases. Aiming to clarify some aspects of its pathogenetic mechanisms, our study focused on the assessment of redox status in dogs, the main reservoir for Leishmania infantum. Forty-five dogs from an endemic area in southern Italy were divided into four different groups (from mild disease with negative to low positive antibody levels to very severe disease with medium to high positive antibody levels) according to the LeishVet group guidelines. Their plasma and/or sera were tested for reactive oxygen species (ROS), namely the superoxide anion (O2−), reactive nitrogen species (RNS), such as nitric oxide (NO) and hydroperoxides (ROOH), as well as activity of the detoxifying enzyme superoxide dismutase (SOD), and total nonenzymatic antioxidant capacity, as determined by the ferric reducing-antioxidant power (FRAP) assay. O2− generation was significantly (p < 0.05) reduced in leishmaniasis-affected dogs independently of the clinical stage, while NO production was stimulated (p < 0.05) only in II and III stage patients. No difference could be found for the levels of hydroperoxides and SOD activity between healthy and pathological subjects. FRAP values were lower in affected dogs but only in stage II. Taken together, although we demonstrated that several redox status parameters are altered in the plasma of dog affected by leishmaniasis, the oxidative stress changes that are observed in this disease, are possibly mainly due to cellular blood components i.e., neutrophils responsible for the elimination of the parasite. Further studies are required to assess the clinical values of the collected data.